Turtle bread - Kim-Joy, 1991- (Dark Horse Books, a division of Dark Horse Comics LLC, 2023)
When Yan stumbles upon Baking Club her social anxiety tries to keep her away, but the bakers encourage her to come out of her shell, especially the caring and supportive Bea, and soon Yan discovers her new friends may need her too.